Perinatal palliative care following prenatal diagnosis of severe fetal anomaly: a new family-centered approach in a level III Portuguese hospital - Diana Paula Gomes Guimarães; Maria Hercília Ferreira Guimarães Pereira Areias; Carla Maria de Almeida Ramalho; Maria Manuela Rodrigues (Hygeia Press di Corridori Marinella, 2018)
Perinatal palliative care (PNPC) is an emerging field that aims to improve the quality of life of families affected by an antenatal diagnosis incompatible with long-term survival through a specialized, multidisciplinary approach and holistic and emotional support. An advance care planning begins at the moment of diagnosis and continues in the postpartum period addressing comfort measures to alleviate pain, psychological support for family members and the collection of mementos that allow parents to make lasting memories of their child. PNPC is also an integral part of the Newborn Individualized Developmental Care and Assessment Program (NIDCAP) in Obstetrics and Neonatology. Since 1997, there are more than 300 programs described, tailored to the newborn's best interest. Up to now, providers often feel difficulties in the implementation of PNPC programs, given the lack of evidence-based quantitative empirical studies that are necessary to establish the best model of care. Obstacles to palliative care include diagnostic and prognostic uncertainty and logistic obstacles related to interdisciplinary collaboration. Literature also suggests a great discrepancy involving end-of-life decisions between different countries. This paper presents an overview of the first PNPC program implemented in a level III Portuguese neonatal intensive care unit (NICU) with two case studies providing a distinctive perspective on the support and care needed.  It also seeks to serve as a resource for other institutions since there are no well-established and published guidelines regarding PNPC in Portugal. It is also important to include obstetric residents, midwives, medical students and nursing students in the provision of palliative care so this model of care can be incorporated into future practices.